Sistem Pencegahan Kebakaran: Evaluasi Terhadap Kapasitas Personel, Keandalan Sensor, dan Sarana Pendukung - Muhammad Furqon Karmijono; Arya Akira Kusuma; Nawang Kalbuana (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2025)
Airports are strategic areas with high levels of activity involving aircraft, operational vehicles, fuel,and large-scale human mobility, making them highly susceptible to fire risks. This study highlightsthe importance of integrating competent human resources, reliable early detection systems, andadequate supporting facilities to form an effective fire prevention system. Firefighters and airportpersonnel are required to have physical readiness, high discipline, and a thorough understanding ofoperational procedures to respond quickly and appropriately to potential hazards. On the otherhand, the use of strategically placed sensors and surveillance cameras is key to detecting fires earlybefore they become major incidents. The availability of supporting facilities such as hydrantsystems, personal protective equipment, and evacuation routes are also vital elements in supportingthe firefighting and emergency evacuation processes. Analysis results indicate that weaknesses inany of these aspects can directly impact the effectiveness of the safety system. Therefore, sustainedefforts are needed to strengthen collaboration among these three key elements to ensurecomprehensive and sustainable aviation operational safety.